Heterogeneity of T-cell beta-chain gene rearrangements in human leukaemias and lymphomas. - Rabbitts, T H (1985)
The state of T-cell receptor beta-chain gene rearrangement in human T-cell leukaemias has been analysed. All forms of leukaemia tested (T-CLL, ALL, PLL, Sezary syndrome and ATL) exhibit rearrangements of C beta genes confirming the clonality of these neoplasias. However we find no evidence for common gene rearrangements nor for restricted rearrangement patterns within this type of neoplasia. We find evidence of T-cells with C beta 1 and C beta 2 rearrangements, sometimes associated with Igh JH rearrangements, but several cases of T-cell leukaemia with a marker inversion of chromosome 14 (q11;q32) do not have Igh JH rearrangements. The results suggest that TCR beta gene rearrangement occurs early in T-cell ontogeny but that this rearrangement is most often irrelevant to leukaemogenesis.